2013
DOI: 10.1080/15402002.2013.821654
|View full text |Cite
|
Sign up to set email alerts
|

Homework Schedule: An Important Factor Associated With Shorter Sleep Duration Among Chinese School-Aged Children

Abstract: This study was designed to examine the hypothesis that homework schedule has adverse impacts on Chinese children's sleep-wake habits and sleep duration. A random sample of 19,299 children aged 5.08 to 11.99 years old participated in a large, cross-sectional survey. A parent-administered questionnaire was completed to quantify children's homework schedule and sleep behaviors. Generally, it was demonstrated that more homework schedule was significantly associated with later bedtime, later wake time, and shorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…[1,3] Sleep deprivation has also been reported among children, especially with relation to the homework schedule. [4,5] Diagnosis of sleep disorders and sleep deprivation is important in children as they have been found to be associated with daytime napping, cardiovascular morbidity, attention deficit hyperactivity disorder (ADHD), and obesity. [6][7][8] Indian data using the sleep questionnaires suggests that around 13% of toddlers have sleep problems, most common being the night awakenings.…”
Section: Introductionmentioning
confidence: 99%
“…[1,3] Sleep deprivation has also been reported among children, especially with relation to the homework schedule. [4,5] Diagnosis of sleep disorders and sleep deprivation is important in children as they have been found to be associated with daytime napping, cardiovascular morbidity, attention deficit hyperactivity disorder (ADHD), and obesity. [6][7][8] Indian data using the sleep questionnaires suggests that around 13% of toddlers have sleep problems, most common being the night awakenings.…”
Section: Introductionmentioning
confidence: 99%
“…Duration of sleep is not static and it shortens with the growing age, especially among children [1], [2], [3], [4]. Reduction of sleep with the growing age can be ascribed to a number of factors that include not only biological but also environmental factors e.g., age related natural decline in sleep need, changes in presleep behavior such as–watching TV or spending time on screens or burden of the school-work [2], [5], [6]. Among these, watching television or spending time with a screen before bed (screen time) is known to reduce the total sleep time and to delay the sleep onset [2], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that children sleeping less were likely to have a sedentary and inactive lifestyle coupled with more time spent on watching TV and homework completion (Li et al, 2014; Jiang et al, 2015; Lin et al, 2018). Reciprocally, more time spent on TV viewing and finishing homework may delay children’s bedtime and shorten their sleep duration (Li et al, 2007; Calamaro et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient sleep among school-aged children may lead to low levels of participation in daily activities or a lack of balanced engagement in a variety of daily activities (Ortega et al, 2011; Engle-Friedman, 2014). However, the existing literature on the relationship between sleep duration and activity participation is primarily limited to specific types of physical or educational activities that have been examined across disparate studies (Li et al, 2014; Jiang et al, 2015; Khan et al, 2015; Lin et al, 2018). Furthermore, these studies did not examine the relationships between sleep duration and the levels of children’s involvement in activities; instead, the participation duration or frequency has been operationalized in most of the studies.…”
Section: Introductionmentioning
confidence: 99%